2010
DOI: 10.1086/652759
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug‐ResistantAcinetobacter baumannii:An Emerging Pathogen among Older Adults in Community Hospitals and Nursing Homes

Abstract: The prevalence and resistance of Acinetobacter species are increasing in the community. Patients with resistant isolates are selectively discharged to nursing homes and long-term acute-care facilities, introducing resistance to new facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 25 publications
1
118
0
1
Order By: Relevance
“…However, it is important to mention that the U.S. SCOPE study occurred almost 10 years ago, and there have been increases in Acinetobacter infections in U.S. hospitals in recent years (11,26). One other possible explanation is that the higher baseline prevalence of Gramnegative bacteria is related to enhanced use of anti-Gramnegative antibiotics, selecting for bacteria prone to develop multidrug resistance, such as nonfermentative Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to mention that the U.S. SCOPE study occurred almost 10 years ago, and there have been increases in Acinetobacter infections in U.S. hospitals in recent years (11,26). One other possible explanation is that the higher baseline prevalence of Gramnegative bacteria is related to enhanced use of anti-Gramnegative antibiotics, selecting for bacteria prone to develop multidrug resistance, such as nonfermentative Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We could not establish an association between the outbreak and the nursing home. The epidemiology of Acinetobacter infection among nursing home residents is largely unknown (19). At present, there is no consensus regarding recommendations to control MRAB infection or colonization in nursing home residents admitted to a hospital.…”
mentioning
confidence: 99%
“…Sengstock and colleague in a six-year period reported in an increase of Multi-Drug-Resistant Acinetobacter baumannii, a link between increasing antibiotic-resistance, morbidity and mortality, and a transfer between hospital and nursing home and viceversa (Sengstock DM & Al, 2010). The article demonstrated that Acinetobacter baumannii is widespread including hospitals, long-term acute-care and nursing homes, and that the transfer of multidrugresistant strains among health care facilities is bidirectional.…”
Section: Others Organismsmentioning
confidence: 98%